Pengaruh Social Media Marketing dan E-WOM pada Purchase Intention Dimediasi oleh Brand Trust - Aisya Muthia Majid; Widya Prananta (Universitas Sains dan Teknologi Komputer, 2026)
This study examines how social media marketing, electronic word of mouth, and brand trust influence purchase intention among prospective Garnier consumers. Data were collected through a questionnaire distributed to 105 prospective Garnier consumers in Semarang. Respondents were selected using purposive sampling, and the data were analyzed using the SEM-PLS method. The findings indicate that electronic word of mouth has a positive and significant effect on purchase intention. However, social media marketing and brand trust do not have a significant effect on purchase intention. Furthermore, although social media marketing and electronic word of mouth have a positive and significant effect on brand trust, the proposed mediation hypotheses are not empirically supported, indicating that brand trust does not function as an effective mediator in explaining the relationship between social media marketing, electronic word of mouth, and purchase intention. These findings suggest that consumer recommendations and reviews play a greater role in shaping purchase intention than social media marketing activities and brand trust. This study contributes to the development of digital marketing literature and provides practical implications for companies to optimize their electronic word of mouth strategies in an effort to increase consumer purchase intention.